Aspek Perizinan dalam Pendirian Perseroan Terbatas dengan Sistem Online Single Submission - Made Karina Thalia Crisandyna; I Nyoman Sumardika; Desak Gde Dwi Arini (Fakultas Hukum, Universitas Warmadewa, 2020)
The acceleration and increase in investment and business needs to be done by implementing an integrated business licensing service online or online single submission (OSS). This study aims to determine the licensing process of establishing a Limited Liability Company with the OSS system and the constraints faced by the directors in OSS and their mitigation efforts. This research is an empirical legal research using empirical juridical approach type and using primary data sources and secondary data. Data collection is done by direct observation in the field and then analyzed using qualitative analysis methods. The results of this study indicate that the licensing process of establishing a Limited Liability Company is carried out online by accessing the OSS website and completing the data as contained in the system. The OSS Institution will then issue an NIB to obtain a Business License and a Commercial or Operational License including to fulfill the requirements for a Business License and a Commercial or Operational License. Furthermore, the obstacles faced in the OSS system are related to regulatory aspects, system aspects, governance aspects, lack of socialization, additional costs in adjusting the goals and objectives of the Limited Liability Company, and accessing them that occur twice, both online and file submission. In the context of overcoming existing obstacles, a task force was formed consisting of the National Task Force, Ministry / Institution Task Force, Provincial Task Force, District / City Task Force, system renewal, seminars and briefing on the OSS system.